DEVELOPMENT OF A VIRTUAL REALITY GAME FOR VESTIBULAR REHABILITATION WITH SACCADIC EXERCISE - Rahmanda, Muhammad
In the development of the vestibular rehabilitation process using saccadic exercises, challenges arise due to a lack of user engagement and appeal. These issues create barriers to achieving optimal results from saccadic exercises. Therefore, it is essential to seek innovative approaches that can effectively motivate and engage users to enhance the efficacy of the vestibular rehabilitation process through a VR game. Furthermore, in the context of developing a Virtual Reality (VR) game for vestibular rehabilitation using saccadic exercises, there is ambiguity regarding its usability level and potential side effects. This study aims to develop a VR game based on saccadic exercises for vestibular rehabilitation and measure its usability and side effects. The study employs the Design Research Method and the ADDIE model as the research method to provide a comprehensive and systematic explanation of the research. Participants in this study are residency doctors, and it involves experts in the fields of ENT and IT. Data collection is conducted through observations, interviews, questionnaires, and literature studies. The results indicate the successful development of a VR game for vestibular rehabilitation named "Saccadic VR," featuring two mini-games that have been validated for potential use by vertigo sufferers. The software evaluation shows that "Saccadic VR" has a high usability level with a score of 79.5 on the System Usability Scale (SUS) and a very low level of side effects with a score of 12.8 on the Virtual Reality Sickness Questionnaire (VRSQ). These findings suggest that the VR game can be an effective and enjoyable tool for vestibular rehabilitation. However, clinical trials are needed before it can be used by vertigo sufferers in the future.